2012
DOI: 10.1007/s00464-011-2123-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of laparoscopic gastric ischemic conditioning prior to minimally invasive esophagectomy, the LOGIC trial

Abstract: LIC does not translate into an improved perfusion of the gastric conduit tip. The benefits reported from published clinical series suggest that the resistance of the conduit to ischemia occurs through alternative possibly microcellular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In the LOGIC trial, a randomized controlled trial of laparoscopic gastric ischemic conditioning prior to MIE, perfusion of the gastric conduit tip—as measured by laser Doppler fluximetry—was not improved by conditioning, although the number of study patients was only 16 [38]. …”
Section: Surgical Procedures Considerationsmentioning
confidence: 99%
“…In the LOGIC trial, a randomized controlled trial of laparoscopic gastric ischemic conditioning prior to MIE, perfusion of the gastric conduit tip—as measured by laser Doppler fluximetry—was not improved by conditioning, although the number of study patients was only 16 [38]. …”
Section: Surgical Procedures Considerationsmentioning
confidence: 99%
“…Advantages of minimal access approaches to the esophagus include a lower risk of postoperative chest infection, shorter length of stay, quicker return to work and post-operative recovery [2][3][4]. There are cited disadvantages, including higher rates of gastric conduit necrosis and anastomotic leak [5,6]. In addition, there are increasing reports of diaphragmatic herniation following esophagectomy performed using minimally invasive techniques [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, exposure of the gastric tip to ischemic conditions prior to the creation of the anastomosis would avoid acute ischemia and improve blood flow at the time of surgery, thereby decreasing leak rates. While some studies have suggested decreased morbidity with this technique, no significant improvement in leak rates have been identified [29][30][31]. To date, a single prospective study has been completed regarding this question.…”
Section: Prevention and Management Of Anastomotic Leaksmentioning
confidence: 99%
“…To date, a single prospective study has been completed regarding this question. Patients underwent laparoscopic ischemic conditioning followed by minimally invasive esophagectomy, and found no improvement in perfusion of the gastric conduit trip [31]. Further, the concept of intentionally creating ischemia of the conduit has been met with much resistance among surgeons and has failed to gain steam.…”
Section: Prevention and Management Of Anastomotic Leaksmentioning
confidence: 99%